2012
DOI: 10.1590/s0100-72032012000800007
|View full text |Cite
|
Sign up to set email alerts
|

Fatores perinatais associados a recém-nascidos de termo com pH<7,1 na artéria umbilical e índice de Apgar <7,0 no 5º minuto

Abstract: Low Apgar score at the 5th min of life associated with pH<7.1 in the umbilical artery can predict adverse neonatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Data from hospital-based studies found association between cardiotocography alterations indicating nonreassuring fetal status and low Apgar scores. These studies did not find significant association between intercurrences that constitute emergencies such as cord prolapse, true knot, meconium, shoulder dystocia and placental abruption and low Apgar score at birth (27)(28) . However, the intercurrences mentioned above constitute intrapartum emergencies that may require immediate intervention and availability of a specialized team, conditions which are limited or absent in the NDC.…”
Section: Factors Associated With Low Apgar In Newborns In Birth Centermentioning
confidence: 77%
“…Data from hospital-based studies found association between cardiotocography alterations indicating nonreassuring fetal status and low Apgar scores. These studies did not find significant association between intercurrences that constitute emergencies such as cord prolapse, true knot, meconium, shoulder dystocia and placental abruption and low Apgar score at birth (27)(28) . However, the intercurrences mentioned above constitute intrapartum emergencies that may require immediate intervention and availability of a specialized team, conditions which are limited or absent in the NDC.…”
Section: Factors Associated With Low Apgar In Newborns In Birth Centermentioning
confidence: 77%
“…Other studies in Brazil showed that the Apgar score in newborns of mothers with HIV was higher than seven in the first and fifth minute, not being related with the HIV infection. Values less than seven are associated with unfavorable outcomes during childbirth, especially neonatal asphyxia 16,24,30 .…”
Section: Discussionmentioning
confidence: 99%